Comparative analysis of SDC2 and SEPT9 methylation tests in the early detection of colorectal cancer: a systematic review and meta-analysis - Zhang, Jie; Li, Chenhui; An, Yu; Wang, Bing; Liang, Guowei (Frontiers in Medicine, 2024)
Purpose: This meta-analysis aimed to evaluate the comparative diagnostic efficacy of Syndecan-2(SDC2) and Septin-9(SEPT9) in the early detection of colorectal cancer(CRC). Methods: We searched PubMed, Embase, Web of Science, and Cochrane Library databases to identify available publications up to October 2024. A direct head-to-head comparator analysis were performed using the random-effects model. Subgroup analyses and corresponding meta-regressions focusing on sample source, number of patients, region, study design, and methylated detection methods were conducted. Intra-group and inter-group heterogeneity were assessed by Cochrane Q and I2 statistics. Results: 11 articles involving 1,913CRC patients and 2,851 healthy people were included in the meta-analysis. The sensitivity of SDC2 was similar compared to SEPT9 for CRC patients (0.67 vs. 0.71, P=0.61), SDC2 has a similar specificity in comparison to SEPT9 for CRC patients (0.90 vs. 0.91, P = 0.86). In subgroup analysis, stool SDC2 was similar compared to stool SEPT9 for CRC patients (sensitivity of 0.81 vs. 0.80, P=0.92; specificity of 0.93 vs 0.91, P=0.73), plasma SDC2 was similar compared to plasma SEPT9 for CRC patients (sensitivity of 0.57 vs. 0.72, P=0.27; specificity of 0.90 vs 0.89, P=0.89). In the subgroup analysis of clinical staging for colorectal cancer (CRC), the results indicate that there is no significant difference in sensitivity between the two markers for both early (0.7 vs 0.67, P=0.64) and advanced (0.76 vs 0.70, P=0.23) stages of CRC. Conclusions: In our head-to-head comparison meta-analysis, it was found that SDC2 and SEPT9 have similar sensitivity and specificity in the diagnosis of colorectal cancer. However, this result may be influenced by high heterogeneity and further confirmation of this finding is needed through large-scale prospective studies.